2013
DOI: 10.1080/03670244.2013.769099
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Agrobiodiversity, Diet, and Intensification of Smallholder Family Farming in the Highland Andes of Ecuador

Abstract: Methods are needed for helping researchers and farmers to interactively describe and analyze local practices in search of opportunities for improving health, environment, and economy. The authors worked with smallholder family farmers in five Andean villages in Ecuador to apply participatory four-cell analysis (PFCA) in characterizing agrobiodiversity. Margelef and Shannon indices examined ecological richness and evenness, and a simplified 24-hour dietary recall characterized food consumption. Cross-analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 27 publications
7
64
0
4
Order By: Relevance
“…Of the studies reported in Table 1, four examined whether income was a mechanism through which crop diversity was associated with dietary diversity. The results of studies led by Oyarzun et al (2013), Herforth (2010) and Powell (2012) all suggest that the relationship is driven by direct contribution to dietary diversity through home consumption rather than through an effect of income. Jones et al (2014) report that those households dedicating a greater portion of land to cash crop production had greater dietary diversity, they note B(t)he potential to earn income from a new crop may in fact motivate production diversification which could have spin-off benefits for diet diversity^p.9, (Jones et al 2014).…”
Section: Economic Influences On Agrobiodiversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Of the studies reported in Table 1, four examined whether income was a mechanism through which crop diversity was associated with dietary diversity. The results of studies led by Oyarzun et al (2013), Herforth (2010) and Powell (2012) all suggest that the relationship is driven by direct contribution to dietary diversity through home consumption rather than through an effect of income. Jones et al (2014) report that those households dedicating a greater portion of land to cash crop production had greater dietary diversity, they note B(t)he potential to earn income from a new crop may in fact motivate production diversification which could have spin-off benefits for diet diversity^p.9, (Jones et al 2014).…”
Section: Economic Influences On Agrobiodiversitymentioning
confidence: 99%
“…Of the studies which measured dietary diversity at the household or individual level: six reported a positive association with crop diversity (Ekesa et al 2008;Herforth 2010;Powell 2012;Jones et al 2012Jones et al , 2014Oyarzun et al 2013), one reported a positive association in one community but not another (Dewey 1981), and two reported no association (Torheim et al 2004;Remans et al 2011). Keding et al (2012) showed an association between diversity of vegetables cultivated and dietary diversity (number of food groups).…”
Section: Agrobiodiversity For Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…The past 25 years have witnessed a significant evolution from the view of smallholder or peasant livelihoods and their environments as significantly separate from global systems, such as the once common concept of disarticulated economies ( [220]; pp. [32][33][34][35][36][37][38][39][40]. Currently, concepts and conditions highlight the relevance of smallholder connectedness with national and global systems including so-called planetary urbanism.…”
Section: Conclusion: Interactions Of Agrobiodiversity and Smallholdermentioning
confidence: 99%
“…The wide-ranging interactions of agrobiodiversity amid global change encompass: (a) the management, quality, and access to livelihood-related resource inputs (e.g., skills, knowledge, and labor engaged directly with agrobiodiversity and supporting resources, such as soils and water) amid the livelihood diversification of food-growers [12][13][14]; (b) ecosystem services and specifically interactions within agrobiodiversity-supporting ecological systems (plant-soil interactions) [10,15]; (c) crop and food-growing strategies using agrobiodiversity for combined economic, environmental, and cultural rationales [16][17][18][19][20][21] including agrodiversity, which refers to management of environmental variation in agriculture [5,22]; (d) adaptation, resilience, and mitigation in response to climate change [23][24][25][26][27]; (e) biodiversity use and conservation [9,[28][29][30][31][32]; (f) market opportunities [33,34]; and (g) food security and sovereignty together with nutrition and dietary diversity and human well-being [35][36][37][38][39]. Each of the above linkages is receiving increased research and policy interest that includes synthesis treatments of multiple linkage types [40,41].…”
mentioning
confidence: 99%